Peningkatan Kapasitas Perawat dalam Penatalaksanaan Henti Jantung melalui Pelatihan Bantuan Hidup Dasar (BHD): Pengabdian - Jakasmir Girsang; Hotmaria Simanullang; Sondang Selviana Silitonga; Karmila Br Kaban; Tiarnida Nababan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Nurses, as frontline healthcare providers, play a vital role in delivering initial emergency care, including the provision of Basic Life Support (BLS). However, not all nurses possess optimal skills in performing BLS according to established guidelines. This activity aimed to provide education and practical training on BLS to novice nurses at RSUD dr. Djasamen Saragih Pematang Siantar, targeting 35 clinical nurses with less than two years of work experience. The training methods included theoretical lectures, demonstrations, and practical simulations using manikins. Evaluation was conducted through pre-test and post-test methods to assess the improvement in participants' knowledge and skills. The results showed a significant increase in both knowledge and skills scores following the training. Participants also demonstrated high enthusiasm and provided positive feedback regarding the content and delivery of the training. This indicates that BLS training is effective in enhancing nurses’ readiness to manage cardiac arrest cases in the workplace, particularly in the setting of RSUD dr. Djasamen Saragih Pematang Siantar.